RNA-seq Profiling and Co-expression Network Analysis of Long Noncoding RNAs and mRNAs Reveal Novel Pathogenesis of Noise-induced Hidden Hearing Loss. (10th May 2020) - Wei, Wei; Shi, Xi; Xiong, Wei; He, Lu; Du, Zheng-De; Qu, Tengfei; Qi, Yue; Gong, Shu-Sheng; Liu, Ke; Ma, Xiulan
Highlights: Adrenergic pathway is most likely to regulate NIHHL revealed by RNA-seq. GNAS is the targeted mRNA in the adrenergic pathway. GNAS functions downstream of Sept7 . GNAS and Sept7 are specifically up regulated in NIHHL. GNAS and Sept7 regulating adrenergic pathway might reveal pathogenesis of NIHHL. Abstract: Noise-induced hidden hearing loss (NIHHL), one of the family of conditions described as noise-induced hearing loss (NIHL), is characterized by synaptopathy following moderate noise exposure that causes only temporary threshold elevation. Long noncoding RNAs (lncRNAs) mediate several essential regulatory functions in a wide range of biological processes and diseases, but their roles in NIHHL remain largely unknown. In order to determine the potential roles of these lncRNAs in the pathogenesis of NIHHL, we first evaluated their expression in NIHHL mice model and mapped possible regulatory functions and targets using RNA-sequencing (RNA-seq). In total, we identified 133 lncRNAs and 522 mRNAs that were significantly dysregulated in the NIHHL model. Gene Ontology (GO) showed that these lncRNAs were involved in multiple cell components and systems including synapses and the nervous and sensory systems. In addition, a lncRNA–mRNA network was constructed to identify core regulatory lncRNAs and transcription factors. KEGG analysis was also used to identify the potential pathways being affected in NIHHL. These analyses allowed us to identify the guanine nucleotide binding protein alpha stimulating ( GNAS ) gene as a key transcription factor and the adrenergic signaling pathway as a key pathway in the regulation of NIHHL pathogenesis. Our study is the first, to our knowledge, to isolate a lncRNA mediated regulatory pathway associated with NIHHL pathogenesis; these observations may provide fresh insight into the pathogenesis of NIHHL and may pave the way for therapeutic intervention in the future.